Hearing Impairment and Other Health Conditions in Older Adults: Chance Associations or Opportunities for Prevention? - Cruickshanks, Karen J.; Wichmann, Margarete A. (Seminars in Hearing, 2012)
The prevalence of hearing impairment, as well as many other medical conditions, increases with age. Epidemiological evidence also suggests that the prevalence of hearing impairment, cardiovascular disease, and possibly dementia have declined during the 20th century. Differences in disease occurrence by birth year indicate that modifiable risk factors contribute to these diseases and that exposure to these risk factors changed over time. This article discusses the co-occurrence of chronic conditions at older ages, along with their shared risk factors and similar temporal trends. Recognition of these patterns is important for audiologists and other health care professionals who treat these complex patients, as well as for researchers investigating the underlying causes of these diseases. Various lines of evidence linking hearing impairment to other conditions and medication use point to the need for hearing health care to be better integrated with the broader health care system.
Keywords: hearing loss; sensorineural hearing loss; presbycusis; epidemiology; aging